Distinguishing benign mediastinal masses from malignancy in a histoplasmosis-endemic region - Naeem, Fouzia (J Pediatr, 2015)
OBJECTIVE: To describe the characteristics of benign and malignant mediastinal masses, which may predict their etiology and facilitate the safe and timely management of patients, especially those residing in histoplasmosis-endemic regions. STUDY DESIGN: We conducted a retrospective review of the health records of 131 patients aged <19 years who were referred to two tertiary care children's hospitals from 2005-2010 for the evaluation of mediastinal masses. RESULTS: Most patients (79%) had benign masses, including 98 with confirmed or suspected histoplasmosis. Overall, patients with benign etiologies were younger, more likely to be African American, more likely to complain of cough and to have pulmonary nodules by chest computed tomographs than patients with cancer. Patients with malignant disease were more likely to complain of malaise and to have neck swelling, abnormal extrathoracic lymphadenopathy, lymphopenia, anterior mediastinal involvement and/or pleural effusion. Positive histoplasmosis serologic tests were specific but insensitive for a benign etiology. No single clinical, laboratory or radiologic feature was sufficiently sensitive and specific to distinguish between benign and malignant masses. For cancer, however, the presence of lymphopenia, anterior mediastinal involvement or enlarged cervical lymph nodes on computerized tomography had a sensitivity of 93%, specificity of 95%, positive predictive value of 86%, and negative predictive value of 97% for cancer. Sixty-four patients (49%) underwent invasive testing, including 37 (36%) of patients with benign masses. CONCLUSIONS: Patients in this series who had involvement of the anterior mediastinum, lymphopenia or enlarged cervical lymph nodes had a high likelihood of cancer. Expectant management of patients lacking these characteristics may be safe and reduce unnecessary invasive testing.